1957
DOI: 10.1113/jphysiol.1957.sp005705
|View full text |Cite
|
Sign up to set email alerts
|

Ion movements in seminal vesicle mucosa

Abstract: The testicular hormone, testosterone, is required by the seminal vesicles for the production of fructose, citric acid and other characteristic chemical constituents of the vesicular secretion (see Mann, 1954), and also appears to influence the distribution of water in the gland. Thus, after the injection of testosterone propionate in castrated rats the extracellular water of the seminal vesicle tissue was reduced about threefold, almost to the value of 138 % found in normal, i.e. non-castrated, rats (Rudolph &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1959
1959
1975
1975

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…Thus, the sum of the Na and K concentrations does not differ from that of C1. Similar values for guinea-pig vesicular fluid were reported by Breuer & Whittam (1957). In view of the fact that the plasma concentration of Na, Cl and K in the guinea-pig are approximately 130, 100 and 6 mm, respectively, the steady-state concentrations of these ions in the vesicular fluid do not conform with a passive (or equilibrium) distribution calculated from the ION TRANSPORT BY SEMINAL VESICLE 20 Nernst equation.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Thus, the sum of the Na and K concentrations does not differ from that of C1. Similar values for guinea-pig vesicular fluid were reported by Breuer & Whittam (1957). In view of the fact that the plasma concentration of Na, Cl and K in the guinea-pig are approximately 130, 100 and 6 mm, respectively, the steady-state concentrations of these ions in the vesicular fluid do not conform with a passive (or equilibrium) distribution calculated from the ION TRANSPORT BY SEMINAL VESICLE 20 Nernst equation.…”
supporting
confidence: 72%
“…The concentrations of Na, K and Cl in guinea-pig seminal vesicular fluid are much lower than those in either the vesicular tissue or the plasma (Breuer & Whittam, 1957). However, although it has been shown that the epithelial cells of guinea-pig seminal vesicle can maintain steady-state intracellular ion concentrations in vitro under both aerobic and anaerobic conditions providing suitable substrates are present in the incubation medium (Breuer & Whittam, 1957;Whittam & Breuer, 1959), the transepithelial transport processes responsible for the elaboration of the vesicular fluid have not been investigated.…”
Section: Introductionmentioning
confidence: 77%
“…Other tissues and cells which possess the ability to transport cations actively both aerobically and anaerobically are frog skin (Leaf & Renshaw, 1957), duck erythrocytes (Tosteson & Robertson, 1956), ascites tumour cells (Maizels, Remington & Truscoe, 1958) and guinea-pig seminal vesicle mucosa (Breuer & Whittam, 1957). A metabolic feature shared by tumour cells and kidney cortex slices of the new-born rabbit and rat is a rate of aerobic glycolysis higher than that of tissues such as liver and kidney cortex of adult animals (see the discussion by Warburg, 1956).…”
Section: Compari8on With Other Ti8suesmentioning
confidence: 99%
“…$ 1 g of water-soluble conjugated oestrogens is equivalent in potency to 0*38 g of sodium oestrone sulphate. red cells (Kahn & Cohen, 1957;Tosteson & Johnson, 1957 a, b) and glutamate had a similar effect on the glandular tissues of the guinea-pig seminal vesicle (Breuer & Whittam, 1957). Physostigmine has been considered to act as both a stabilizer and labilizer of resting membrane permeabilities (see Shanes, 1958).…”
Section: Effects Of Bicarbonate and Glucosementioning
confidence: 99%